2018
DOI: 10.1021/acs.orglett.8b00851
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phthalocyanines through Axial Coordination

Abstract: A novel approach to axially induce chirality on silicon phthalocyanines via a microwave-assisted route is reported. CD analysis provides spectroscopic evidence that chirality is transferred onto both Soret and Q-bands of the phthalocyanine core. A chiral naphthalenediimide ligand was found to induce the largest Cotton effect on the macrocycle absorptions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 35 publications
2
9
1
Order By: Relevance
“…The g-factor ranges between −2 and +2, spanning between 10 −3 and 10 −4 for organic molecules [21]. Derivative 1 has flexible sidechains appended to the aromatic NDI, displaying the largest ellipticity in solution as shown by our previous studies [18]. The absorption pattern of film of 1 from TCE is similar to that in solution.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…The g-factor ranges between −2 and +2, spanning between 10 −3 and 10 −4 for organic molecules [21]. Derivative 1 has flexible sidechains appended to the aromatic NDI, displaying the largest ellipticity in solution as shown by our previous studies [18]. The absorption pattern of film of 1 from TCE is similar to that in solution.…”
Section: Resultsmentioning
confidence: 53%
“…The SiPcs used in this study are shown in Figure 1A. We have recently reported a one-step, microwave-assisted approach to synthesize chiral SiPcs through axial coordination [18]. The three SiPcs used in this study have been synthesized via this method (full characterization in the Materials and Methods section).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations